2020
DOI: 10.1038/s41598-020-64310-y
|View full text |Cite
|
Sign up to set email alerts
|

Topical rifampicin for prevention of deep sternal wound infections in patients undergoing coronary artery bypass grafting

Abstract: Deep sternal wound infections (DSWI), although an infrequent complication, significantly impair postoperative outcomes after coronary artery bypass grafting (CABG) surgery. Among several preventive strategies, topical antibiotic therapy immediately before sternal closure has been strongly advocated. In this retrospective analysis, the incidence of DSWI in 517 patients undergoing isolated CABG and receiving rifampicin irrigation of mediastinum, sternum and suprasternal tissues was compared to an historical cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…177 Other agents worth additional study include polyhexanide and rifampicin in certain patient populations. 178,179 Control blood-glucose level during the immediate postoperative period for all patients. 94 (Quality of evidence: HIGH) Monitor and maintain postoperative blood-glucose level regardless of diabetes status. Maintain postoperative blood-glucose level between 110 and 150 mg/dL.…”
Section: Section 4: Recommended Strategies To Prevent Ssimentioning
confidence: 99%
See 1 more Smart Citation
“…177 Other agents worth additional study include polyhexanide and rifampicin in certain patient populations. 178,179 Control blood-glucose level during the immediate postoperative period for all patients. 94 (Quality of evidence: HIGH) Monitor and maintain postoperative blood-glucose level regardless of diabetes status. Maintain postoperative blood-glucose level between 110 and 150 mg/dL.…”
Section: Section 4: Recommended Strategies To Prevent Ssimentioning
confidence: 99%
“…177 Other agents worth additional study include polyhexanide and rifampicin in certain patient populations. 178,179 …”
Section: Section 4: Recommended Strategies To Prevent Ssimentioning
confidence: 99%
“…In his study done retrospectively, De Santo et al concluded that patients receiving local rifampicin wash of the mediastinum and sternal edges showed significant reduction in the incidence of deep sternal wound infection (0.3% versus 2.1%, P = .0391). ICU stay, hospital stay, and operative mortality were similar between the groups [De Santo 2020].…”
Section: E602mentioning
confidence: 78%